Health-Saving Care for Children in Emergency Situations is an Effective Way to Implement Innovative Approaches to Forming a Completely Developed Generation - Jumaniyazovna, Sharipova Dilara (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the topical problems of providing health-saving assistance to children in emergency situations, the formation of extreme competence in parents who are called upon to provide the first pre-medical medical and social support to children in difficult conditions arising after natural disasters.